Co-varying effects of vegetation structure and terrain attributes are responsible for soil respiration spatial patterns in a sandy forest–steppe transition zone - G. Süle (Copernicus Publications, 2021)
Forest–steppe habitats in central Hungary have contrasting canopy structure with strong influence on the spatiotemporal variability of ecosystem functions. Canopy differences also co-vary with terrain feature effects, hampering the detection of key drivers of carbon cycling in this threatened habitat. We carried out seasonal measurements of ecosystem functions (soil respiration and leaf area index), microclimate and soil variables as well as terrain features along transects for 3 years in poplar groves and the surrounding grasslands. We found that the terrain features and the canopy differences co-varyingly affected the abiotic and biotic factors of this habitat. Topography had an effect on the spatial distribution of soil organic carbon content. Canopy structure had a strong modifying effect through allocation patterns and microclimatic conditions, both affecting soil respiration rates. Due to the vegetation structure difference between the groves and grasslands, spatial functional diversity was observed. We found notably different conditions under the groves with high soil respiration, soil water content and leaf area index; in contrast, on the grasslands (especially in E–SE–S directions from the trees) soil temperature and vapor pressure deficit showed high values. Processes of aridification due to climate change threaten these habitats and may cause reduction in the amount and extent of forest patches and decrease in landscape diversity. Owing to habitat loss, reduction in carbon stock may occur, which in turn has a significant impact on the local and global carbon cycles.